Academic Hope and Psychological Resilience Among University Students - Al-Anzi , Hussein Karim Mohammed; Al-Mayahy, Rawaa Jaafar Abd (Indonesian Journal of Education Methods Development, 2026)
General Background: Academic hope and psychological resilience are central constructs in positive psychology that support students’ adaptation and goal attainment in higher education. Specific Background: University students frequently encounter academic pressures that require cognitive motivation and emotional regulation to sustain performance. Knowledge Gap: Although both constructs are widely studied, limited empirical research has examined their relationship within the context of Iraqi university students. Aim: This study aimed to identify levels of academic hope and psychological resilience and examine their correlational relationship among university students. Results: Using a descriptive correlational design with a stratified random sample of 400 students, findings indicated that students demonstrated high levels of academic hope and psychological resilience, with no significant gender differences in either variable. A statistically significant positive correlation was found between academic hope and psychological resilience. Novelty: The study provides empirical evidence from an Iraqi university context using validated psychometric scales grounded in Snyder’s and Grotberg’s theoretical frameworks. Implications: The findings suggest that fostering academic hope alongside psychological resilience may support students’ academic persistence and psychological well-being in higher education settings. Highlights: University students demonstrate high academic hope and resilience. No significant gender differences were identified. Academic hope is positively correlated with psychological resilience. Keywords: Academic Hope; Psychological Resilience; University Students; Positive Psychology; Higher Education